MULTIPLE FUNGAL AND BACTERIAL INFECTION MIMICKING PUSTULAR PSORIASIS: A SIDE EFFECT OF EXTERNAL CORTICOSTEROID THERAPY FOR PSORIASIS VULGARIS - MAEKAWA, Yoshihiro; NOGAMI, Reiko (Japanese Journal of National Medical Services, 1995)
A 75-year-old Japanese male with a 7-year history of psoriasis vulgaris was referred to the Department of Dermatology, Kumamoto National Hospital for the development of generalized pustular lesions. His 43-year-old eldest son was also being reated for psoriasis vulgaris and psoriasic erythroderma. The patient had been treated with the application of corticosteroid ointment and the formation of pustules forced him to apply the ointment more eagerly, leading to an exacerbation. Although resembling pustular pustulosis, his condition was identified to be cutaneous infections by multiple species of fungi and bacteriae including MRSA. Impairment of cutaneous immunity due to corticosteroids was suspected to be responsible for the cutaneous infections. Comprehensive dermatological skill is required to manage such patients on prolonged corticosteroid treatment.